COLLABORATIVE TEACHING WITH CANVA COMIC STRIPS IN PARAGRAPH WRITING - Adinda Intan Dwi Wulandari; Moh. Hafidz (Tadulako University, 2026)
The purpose of this study is to assess how students at SMP Nurul Ikhlas Abusiri perceive comic strips as an educational resource in the context of collaborative writing instruction enabled by the Canva program. During the academic year 2025-2026, the lead researcher taught seventh-grade English using a descriptive qualitative methodology. Data were collected using a diverse strategy that included semi-structured interviews, surveys, documentation of student assignments, and systematic classroom observations. The findings show that the educator successfully implemented a systematic instructional framework consisting of five separate stages: introduction and familiarization, visual precomposition, linguistic composition, cooperative peer assessment, and concluding adjustments. The combination of visually diversified comic panels and Canva's digital design platform acted as an effective learning aid, tackling common student writing issues such as restricted vocabulary and disconnected sentence construction. Participants had notably positive emotional, intellectual, and creative reactions, indicating that immediate peer interaction and visual support reduced apprehension about writing, fostered a comfortable educational environment, and significantly increased self-confidence in their writing abilities. The findings indicate that adding digital platforms with diverse modalities into collaborative writing processes constitutes a significant development for second language acquisition in secondary education.